A clinical carepath for obese pregnant women: a pragmatic pilot cluster randomized controlled trial. (2nd December 2019) - McDonald, Sarah D.; Viaje, Kristen A.; Rooney, Rebecca A.; Jarde, Alexander; Giglia, Lucia; Maxwell, Cynthia V.; Small, David; Pearce Kelly, Tracy; Sabatino, Lisa; Thabane, Lehana
Abstract: Objectives: Obese women are at increased risks for complications during pregnancy, birth, and in their infants. Although guidelines have been established for the clinical care of obese pregnant women, management is sometimes suboptimal. Our goal was to determine the feasibility of implementing and testing a clinical carepath for obese pregnant women compared to standard care, in a pilot cluster randomized controlled trial (RCT). Methods: A pragmatic pilot cluster RCT was conducted, randomly allocating eight clinics to the carepath or standard care for obese pregnant women. Women were eligible if they had a pre-pregnancy body mass index (BMI) of ≥30 kg/m 2 and a viable singleton <21 weeks. The primary outcomes were the feasibility of conducting a full-scale cluster RCT (defined as >80%: randomization of clinics, use in eligible women, and completeness of follow-up) and of the intervention (defined as >80%: compliance with each step in the carepath and recommendation of the carepath by clinicians to a colleague). Results: All eight approached clinics agreed to participate and were randomized. Half of the intervention clinics used the carepath, resulting in <80% uptake of eligible women. High follow-up (99.5%) was achieved, in 188 of 189 women. The carepath was feasible for numerous guideline-directed recommendations for screening, but less so for counseling topics. When the carepath was used in the majority of women, all clinicians, most of whom were midwives, reported they would recommend it to a colleague. The intervention group had significantly higher overall adherence to the guideline recommendations compared to control (relative risk: 1.71, 95% confidence interval: 1.57–1.87). Conclusions: In this pragmatic pilot cluster RCT, a guideline-directed clinical carepath improved some aspects of care of obese pregnant women and was recommended by clinicians, particularly midwives. A cluster RCT may not be feasible in a mix of obstetric and midwifery clinics, but may be feasible in midwifery clinics.